Holocene Monsoonal Variations Over Southern India: Looking Into Its Antecedents - Resmi, M. R.; Achyuthan, Hema; Deopa, Hritika (Frontiers in Earth Science, 2022)
A proper understanding of the paleoclimatic variability in the Southern Peninsular India demands a high-resolution paleoclimate reconstruction record. Hence, in this paper, we compiled all the available paleoclimate records from various locations across the Southern India that receives the southwest and the northeast monsoon. We delineated the southwest monsoon (SWMR) and Northeast monsoon (NEMR) variations within the Holocene Period based on the existing paleoclimatic record from this region. Paleoclimate records are primarily based on various paleoclimate archives and proxies. A detailed study of these variations unravels, (i) that SWMR gradually intensified since the younger dryas during the Early Holocene period. On the contrary, NEMR records indicate a dry phase during the same period. (ii) During the mid-late Holocene, precipitation in SWMR-dominated regions decreased, whereas precipitation in NEMR-dominated regions shows an increasing trend. (iii) Then, in the late Holocene Period, SWMR exhibits an overall wet phase with a few drier periods, and NEMR shows an intense dry period with shorter wet phases, which can be correlated to the demise of Chola dynasty, in the Southern India.